The Determing Activation Energy of Total Oxidation Reaction of m-xylene over La0,7Sr0,3BO3 (B = Mn, Fe, Ni) Perovskite Catalysts - Huyen, Tran Thi Thu; Luyen, Tran Thi; Mai, Nguyen Thi Tuyet (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
Perovskite-type oxides containing rare earth ions and transition metals are of interest for catalytic oxidation and reduction reactions associated with automotive exhaust emission control. They are known to exhibit a good catalytic activity in the total oxidation reaction of carbon monoxide or hydrocarbon and removal of nitrogen oxides. By partially substitution of A and B ions of the perovskite with others, a wide variety of mixed oxides A 1-x A ’ x B 1-y B ’ y O 3 can be obtained, allowing the systematic modification of the catalytic properties. We presented the preparation and the catalytic properties of and La 0.7 Sr 0.3 BO 3 (B = Mn, Fe, Ni) perovskites in total oxidation of m-xylene in previous report. Obtained results showed that they exhibit a good catalytic activity in total oxidation of  m-xylene at relatively low reaction temperature. In present work, the activation energy of total oxidation reaction of m-xylene over these catalysts are determined. The results show that the activation energy of studied catalyst is ranging about from 11.5 to 13.4 kcal/mol. The replacement of Mn by Fe and Ni in La 0.7 Sr 0.3 MnO 3  perovskite catalyst reduces the catalytic property of  La 0.7 Sr 0.3 MnO 3 catalyst and increases the activation energy of the total oxidation reaction of m-xylene.